Education with Human Touch - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Obstetrics and gynecology education deals with the physiological processes and pathology equally. Three competency domains as knowledge, skills and attitudes are equally important. Scientific and ethical clinical practice survives only with the education that has human touch.